A New Synthetic Peptide Having Two Target of Antibacterial Action in E. coli ML35 - Barreto-Santamaría, Adriana; Curtidor, Hernando; Arévalo-Pinzón, Gabriela; Herrera, Chonny; Suárez, Diana; Pérez, Walter H.; Patarroyo, Manuel E. (Frontiers in Microbiology, 2016)
The increased resistance of microorganisms to the different antimicrobials available to today has highlighted the need to find new therapeutic agents, including natural and/or synthetic antimicrobial peptides. This study has evaluated the antimicrobial activity of synthetic peptide 35409 (RYRRKKKMKKALQYIKLLKE) against S. aureus ATCC 29213, P. aeruginosa ATCC 15442 and E. coli ML 35 (ATCC 43827). The results have shown that peptide 35409 inhibited the growth of these three bacterial strains, having 16 fold greater activity against E. coli and P. aeruginosa, but requiring less concentration regarding E. coli (22 µM). When analyzing this activity against E. coli compared to time taken, it was found that this peptide inhibited bacterial growth during the first 60 min and reduced CFU/mL 1 log after 120 min had elapsed. This antimicrobial peptide permeabilized the E. coli membrane by interaction with membrane phospholipids, mainly phosphatidylethanolamine, inhibited cell division and induced filamentation, suggesting two different targets of action within a bacterial cell. Cytotoxicity studies revealed that peptide 35409 had low hemolytic activity and was not cytotoxic for two human cell lines. We would thus propose, in the light of these findings, that the peptide 35409 sequence should provide a promising template for designing broad-spectrum antimicrobial peptides.